2008
DOI: 10.1016/j.jvs.2008.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Optimal carotid duplex velocity criteria for defining the severity of carotid in-stent restenosis

Abstract: The optimal DUS velocity criteria for in-stent restenosis of >or=30%, >or=50%, and >or=80% were the PSVs of 154, 224, and 325 cm/s, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
77
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(84 citation statements)
references
References 23 publications
2
77
0
5
Order By: Relevance
“…Moreover, the duplex velocity criterion for carotid ISR of $50% was defined as $150 cm/second in PSV, lower than the criterion used in recent studies. 21,22 Thus, it is very unlikely that the incidence was underestimated. Given the 6.4% incidence of ISR or TVR in patients who did not receive cilostazol periprocedurally, similar to that reported previously, the lower incidence of ISR in the cilostazol-treated patients might have affected our results.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the duplex velocity criterion for carotid ISR of $50% was defined as $150 cm/second in PSV, lower than the criterion used in recent studies. 21,22 Thus, it is very unlikely that the incidence was underestimated. Given the 6.4% incidence of ISR or TVR in patients who did not receive cilostazol periprocedurally, similar to that reported previously, the lower incidence of ISR in the cilostazol-treated patients might have affected our results.…”
Section: Discussionmentioning
confidence: 99%
“…11 However, the impact of arterial stenting on DUS signal delivery and detection has not yet been sufficiently evaluated, and increased flow velocity and overestimation of moderate stenosis have been reported. 22,23 In these investigations, computed tomography angiography (CTA) or magnetic resonance angiography (MRA) measurements (or the endarterectomized specimen) were compared with DUS measurements. In the present investigation, DUS measurements were evaluated only with DUS, but under strictly standardized conditions.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 A PSV value ranging from 300 to 450 cm/s has been associated with 70% to 80% stenosis. Our investigation showed a PSV of 334 cm/s for a 73.8% stenosis, which is in accordance with described clinical findings.…”
Section: Discussionmentioning
confidence: 99%
“…Typical postprocedural carotid duplex sonographic velocities after successful stenting have been defined. Lal et al 3 proposed a PSV threshold of 150 cm/s or higher and a PSV ratio of 2.1 or higher for detecting residual poststent stenosis of 20% or greater; Setacci et al 12 proposed using a PSV threshold of higher than 105 cm/s for detecting poststent stenosis of 30% or greater, and AbuRahma et al 14 proposed a PSV of higher than 154 cm/s to define poststent stenosis of greater than 30%. We report reference ranges for carotid duplex sonographic velocities indicative of less than 20% stenosis on completion angiography that are consistent with these previously published criteria and confirm the observation that angiographically normal stented carotid arteries may have elevated sonographic velocities compared with native carotid arteries.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Carotid duplex sonography is the standard diagnostic test used for surveillance after carotid artery revascularization procedures, including carotid endarterectomy and carotid artery stenting. Several studies have shown elevated sonographic velocities after stenting in the absence of angiographically proven restenosis, [3][4][5][6] and whereas there have been several proposed distinct velocity-based diagnostic criteria for in-stent restenosis after stenting, 3,4,[6][7][8][9][10][11][12][13][14] most velocity criteria were developed shortly after stent placement. Few studies have explored whether Doppler flow T Article includes CME test velocities within successfully stented carotid arteries vary over time, thereby necessitating separate velocity criteria depending on the time from stent placement, or whether there are identifiable factors that influence poststent velocities.…”
mentioning
confidence: 99%